NEW GEOLOGICAL DATA FROM GORGONA ISLAND (NORTHERN TYRRHENIAN SEA) - Orti, Letizia; Morelli, Marco; Pandeli, Enrico; Principi, Gianfranco (Ofioliti, 2002)
The oceanic HP/LT metamorphic units cropping out in the Gorgona Island (Tuscan Archipelago) are an important element to define the Alps-Apennines geological boundary. In particular, they could represent a link between the Alpine Schistes Lustrés of the Corsica Island and the similar oceanic metamorphic units of the inner part of the Northern Apennines (e.g. Argentario Promontory, Giglio Island, Elba Island). The Gorgona Island tectonic stack includes two main units (the Metasedimentary Unit and the overlying Metaophiolitic Unit) separated by a north-eastward dipping cataclastic-mylonitic shear zone. These units are imprinted by a polyphased tectono-metamorphic evolution ranging from an Oligocene blue-schists event to the ?Miocene re-equilibration and exhumation in the green-schists facies. The new 1:2.000 mapping and the litostratigraphical, structural, petrographical studies presented here allow to improve the geological knowledge of the island. In the Punta Gorgona Calcschists (Metasedimentary Unit) three lithofacies were distinguished and mapped. Their areal distribution and the structural data (e.g. “s” and “z” - type asymmetries of the parassitic folds, the relationships between bedding and cleavages) evidenced several NW-vergent folds in the overturned limb of the D2 mega-fold in the central-southern part of the island. Moreover, during the D2 event, which exhumed and deformed the D1 structures, shearing produced a mylonitic horizon between the two units. During the following extensional stages, an evident inversion of movement along the mylonitic horizon took place and produced a cataclastic texture. Later, weak folds, mainly E-W joints and possible high angle normal faults affected both units. The reconstructed metamorphic-tectonic evolution is compared with that defined for “Alpine Corsica” and for the Northern Apennines chain. From a stratigraphic point of view the data suggest that the Cala di Pancia Sandstones may represent the stratigraphic top of the Metasedimentary Unit, and its probable lateral-vertical transition to part of the Punta Gorgona Calcschists are inferred. The Authors also discuss the possible correlations of the Gorgona Units with other Ligurian-Piedmontese Units cropping out in Corsica, in the Tuscan Archipelago and in the Northern Apennines.